Innovation, Alliances and Management of Halal Products as Strategies to Increase MSME Competitiveness in the Era of the Covid-19 Pandemic - Khairawati, Salihah; Marianti, Dina Juni; Wijiharta (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This study discusses the efforts made by MSMEs in the culinary field in the aspects of innovation, alliances and halal products to maintain their business during the pandemic, then these efforts are compiled into MSME recommendations to increase the competitiveness of the New Normal Era. Methodology/approach – This writing uses a descriptive qualitative method using a literature study of Miles Hubermen's data reduction model with trigulation validity. The author conducted semi-structured interviews by determining the object of the interview based on the criteria. Findings – The results of the writing are that the MSMEs in the culinary field that the writer interviewed did product innovation, organizational innovation and marketing innovation, some made alliances and all participants carried out halal product management. Novelty/value – This writing contributes to MSMEs to increase the competitiveness of the New Normal Era and improve knowledge, especially the management of product innovation, organizational innovations, marketing innovations, alliances and halal products